2007
DOI: 10.1021/es070382+
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation of Arsenate with Metal Oxides. 2. Nature, Mineralogy, and Reactivity of Iron(III) Precipitates

Abstract: Coprecipitation of arsenic with iron or aluminum occurs in natural environments and is a remediation technology used to remove this toxic metalloid from drinking water and hydrometallurgical solutions. In this work, we studied the nature, mineralogy, and reactivity toward phosphate of iron-arsenate coprecipitates formed at As(V)/Fe(III) molar ratios (R) of 0, 0.01, or 0.1 and at pH 4.0, 7.0, and 10.0 aged for 30 or 210 days at 50 degrees C and studied the desorption of arsenate. At R = 0, goethite and hematite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 30 publications
3
84
0
1
Order By: Relevance
“…Many studies have been carried out on the formation, surface properties, mineralogy and reactivity of coprecipitates formed by the interaction of low molecular mass organic ligands (LMMOLs; e.g., oxalate, tartrate, citrate and tannate) with Al and/ or Fe hydrolytic products (Violante et al, 2003;2007;Violante, 2013 Acetate < glutarate < succinate = phthalate < glycine < tricarballilate < malonate < acetylacetone < glutamate < aspartate < oxalate < salicylate = malate < tannate < citrate < tartrate. Table 2).…”
Section: Coprecipitates Of Organic Anions With Hydrolytic Products Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out on the formation, surface properties, mineralogy and reactivity of coprecipitates formed by the interaction of low molecular mass organic ligands (LMMOLs; e.g., oxalate, tartrate, citrate and tannate) with Al and/ or Fe hydrolytic products (Violante et al, 2003;2007;Violante, 2013 Acetate < glutarate < succinate = phthalate < glycine < tricarballilate < malonate < acetylacetone < glutamate < aspartate < oxalate < salicylate = malate < tannate < citrate < tartrate. Table 2).…”
Section: Coprecipitates Of Organic Anions With Hydrolytic Products Ofmentioning
confidence: 99%
“…Violante et al (2006Violante et al ( , 2007Violante et al ( , 2009b evidenced that the mineralogy, the surface properties and chemical composition of the AlAs(V) or Fe-As(V) coprecipitates were affected by the initial pH, initial As/Al (Fe) molar ratio (R) and aging. These authors demonstrated that less As(V) was replaced by P from As(V) iron and/or aluminum coprecipitates than from previously formed iron and/ or aluminum oxides on which As(V) was sorbed.…”
Section: Coprecipitates Of Organic Anions With Hydrolytic Products Ofmentioning
confidence: 99%
“…Some studies were carried out by Violante et al [54][55][56] on samples formed by coprecipitating arsenate with aluminum and/or iron. These authors demonstrated that less ) of arsenite and arsenate in absence and presence of competing anions (initial anion/arsenite or arsenate molar ratio of 1.0), at pH 6.0 and 20°C, and efficiency (%) (i.e., efficiency of the anions in inhibiting arsenite or arsenate sorption on sorbent surfaces) on ferrihydrite (A) [52], noncrystalline Al oxides (B) [53], and MgFe-LDH (C) [26,27] Arsenite Arsenate Anion Sorption (mmol kg arsenate was replaced by phosphate from arsenate iron and/or aluminum coprecipitates than from previously formed iron and/or aluminum oxides on which arsenate was sorbed [57].…”
Section: Coprecipitation Versus Sorptionmentioning
confidence: 99%
“…While arsenate mobility is limited by chemisorption to the surface of several common minerals, such as iron (Fe) and aluminium oxy(hydr)oxides, arsenite is effectively adsorbed by a fewer minerals and less strongly retained on the surfaces [59]. The strong affinity of Fe oxy(hydr)oxides towards As and the formation of Fe-As co-precipitation products have been widely studied, and the co-precipitation of Fe oxy(hydr) oxides including As and/or other contaminants is a method commonly exploited in As removal plants [26,67].…”
Section: Introductionmentioning
confidence: 99%